Japan : Financial Sector Assessment Program: Technical Note on Financial System Spillovers. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This Spillover Report analyses the potential channels of financial system spillovers in Japan that policymakers should keep in mind. The report also highlights some of the potential challenges faced by Japanese financial institutions in managing risks developed owing to overseas exposure. The Executive Board acclaims the importance of an institutional and regulatory framework in managing spillover channels. The report is a guideline as to how Japan developed to win its position in the world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet